Percepção dos gestores sobre fatores contingenciais no orçamento empresarial e uma proposta de adaptação em indústria do oeste do Paraná - Trocz, Pedro Junior de Oliveira (2021)
Social, technological, and economic changes cause the improvement of the business management methodology for those who seek market survival. Among the management accounting artifacts that help managers is the corporate budget, a tool that supports companies in reaching their previously defined goals. To successfully prepare the budget pieces, it is inherent to take into account the internal and external contingency factors that surround the company, as well as to adapt to their impacts. Thus, the general objective of this study was to analyze the managers' perception of the contingential factors in the current corporate budget and a proposal for adaptation. To this end, a descriptive, applied research was adopted, with case study procedures in a qualitative approach. The case unit was an industry in the field of equipment used for the artificial cooling of bulk grains and seeds located in the western region of Paraná. Data were collected by means of interviews with a semi-structured script applied to four managers responsible for planning and also by means of budget reports for the period 2020. For the data analysis the content analysis technique of Bardin (2002) was used, as well as the Atlas.ti 7.0 and Excel softwares. Thus, the results showed that the factors Environment, Technology, Structure and Strategy caused effects on the budget structure of sales, costs and expenses, and also for the adoption of a budget with reviews, in the same way, for the company to use the budget for planning functions and resource allocation. In the results of the corporate budget adaptation proposal it was observed that the managers evaluated it with zeal and satisfaction, stating that: the typology allows to project data without taking into account previous information and makes the increment of new values flexible; the budget structure discriminates the nature of costs, expenses and revenues per sector and allows the increment of new values to the planning; the set of tools in the proposal reduces the time consumption to prepare the planning and helps in the process of environmental adaptation. Thus, contingency factors are present in the organization's internal and external environment and influence its survival and growth by configuring and shaping the company's organizational structure as a result of their effects on the corporate budget. The study provided contributions in the business field due to the fact that it elaborated a business budget proposal in face of the internal and external factors that surround the organization's management. And also contributions in the academic field, with the line of research management accounting and control of organizations, by testing the contingency theory and promoting similarity confirmations between theory and practice in the daily life of companies.